The Existence of PowerPoint Media toward Popular Scientific Article Writing Learning for Grade VIII Students of SMP Negeri 27 Medan - Manalu, Nora Feretty Anggel; Sianturi, Puput Adelina; Ginting, Selvi Sari Br; Silaban, Tasya Aflina; Hutagalung, Trisnawati; Azizah, Nurul (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe: 1) the benefits of PowerPoint media in learning to write popular scientific articles; 2) the effectiveness of PowerPoint media in improving students' understanding of popular scientific articles; 3) the impact of using PowerPoint on students' interest and involvement in the learning process of writing popular scientific articles. The research activities were carried out in the odd semester of the 2025/2026 academic year by applying a qualitative descriptive approach. The subjects of this study were all eighth grade students of SMP Negeri 27 Medan. An Indonesian language teacher acted as the main informant. Research data were collected using two non-test instruments, namely simple observation guidelines and semi-structured interview guidelines. The observation guidelines were used for observation activities to obtain data on the use of PowerPoint media in learning to write popular scientific articles, data on the effectiveness of PowerPoint media in improving students' understanding of popular scientific articles, and data on the impact of using PowerPoint on students' interest and involvement in the learning process of writing popular scientific articles. Semi-structured interviews were used to obtain validation data for the observation guideline instrument. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research findings show: 1) PowerPoint media is useful because teachers can easily clarify the structure of popular scientific articles by visualizing elements such as titles, leads, body paragraphs, and conclusions systematically so that they are easily accepted by students; 2) PowerPoint media is effective in increasing students' understanding of popular scientific articles; 3) the use of PowerPoint has an impact on students' interest and involvement in the learning process of writing popular scientific articles.